The Development of Mobile Application for College Event Attendance System / Nur Irisya Anis Mohd Akin ... [et al.] - Mohd Akin, Nur Irisya Anis; Ahmad, Marina; Manaf, Maznie; Arifin, Noorfadzilah; Mohd Zain, Nor Asma (Unit Penerbitan UiTM Kelantan, 2024)
Events organised by students’ residential colleges require the participants to sign in to the event. The existing sign-in system is by taking attendance manually, and the attendance records are stored in a physical file. Therefore, the objective of this study is to develop a mobile application to automate the signing process and events’ data management. This study is motivated by the lengthy waiting time for participants to stand in a long queue and manually sign on a piece of paper. The attendance paper is then stored physically in a file, which is exposed to misplacement, damage, and loss. Additionally, retrieving and analysing attendance and event data also becomes cumbersome when the physical file must be manually sorted. To overcome these problems, College Events Attendance Monitoring System is developed by following the Waterfall model, which has a stable cycle of development where the phases are carried out sequentially. Event organisers can add, edit, and delete events’ data from the system. Students can register as participants to an event, sign in to the event, rate the event, and see the history of events attended through the mobile app. As part of the security, user registration authentication is ensured through One-Time Passwords (OTPs). End-user evaluations indicated high satisfaction with the app’s features and usability.